VD_FINDINFO AVS 49/19 - 12/2020 vom 24. April 2020 - VD Tribunal cantonal (2020)
REJET DE LA DEMANDE, DÉCISION DE COTISATIONS ARRIÉRÉES, INTÉRÊT MORATOIRE | 10 LAVS, 14 LAVS, 24 RAVS, 25 RAVS, 41bis RAVS